PENGARUH PENERAPAN KURIKULUM TERHADAP MOTIVASI DAN MINAT BELAJAR SISWA DENGAN ANGKET SKALA LIKERT PADA MATEMATIKA - Della Putri, Anggraeni; Panglipur, Indah Rahayu; Marsidi, Marsidi (Universitas Insan Budi Utomo, 2021)
The effect of curriculum application on student motivation and interest in learning with a Likert scale questionnaire in mathematics at SMK Trunojoyo Jember, this research is based on the motivation and interest in student learning at SMK Trunojoyo Jember, especially in class IX BDP after implementing the 2013 Curriculum. student interest in learning and is one of the advantages of student interest in boosting motivation and interest in learning through a learning process that is oriented towards developing active, creative, and enjoyable learning for students. This study aims to determine whether or not the 2013 Curriculum has been applied to students' motivation and interest in learning. The research was conducted at SMK Trunojoyo Jember. The variables used in this research are 2013 Curriculum (Y), Learning Motivation (X1), and Learning Interest (X2). This research is an ex post facto research with quantitative research type. In this study, the authors used the Multiple Paradigm Approach research design. Based on the results of data analysis and the discussion that has been described, the conclusion is that by using the F test with manual calculations, get the Fcount value greater than the Ftable value or 15.10> 3.35, which means that Ho is rejected, so it can be denied that there is an effect of the implementation of the 2013 Curriculum. towards students' motivation and interest in learning.